Osteogenesis Improvement of Gelatin-Based Nanocomposite Scaffold by Loading Zoledronic Acid - Abdulahy, Sayed Behnam; Esmaeili Bidhendi, Mona; Vaezi, Mohammad Reza; Moosazadeh Moghaddam, Mehrdad (Frontiers in Bioengineering and Biotechnology, 2022)
Bisphosphonates (BPs) such as Zoledronic acid (ZA) are a subset of synthetic small molecules, which are now marketed as the main drugs to stimulate the growth and differentiation of osteoblast cells, thereby increasing bone formation as well as preventing bone loss. Also, Halloysite Nanotubes (HNTs)-polymer composites have attracted a lot of attention due to their high surface-to-volume ratio, low density, and high hydrophilicity, and are easily dispersed in hydrophilic biopolymers. In addition, their ability to carry enough amounts of drugs and the ability to control release has been demonstrated. Based on studies, the Gelatin-based scaffold with Halloysite nanotube (HNT) has the capacity as a drug carrier and Zoledronic acid (ZA) sustains release. Previous studies show that using ZA intravenously has some severe side effects and limitations. But by attention to the advantages of its osteogenesis, the current study has been done in order to reduce the side effects of local delivery of it. The 3-dimensional scaffolds were prepared by the Freeze-drying method. Characterization methods such as FE-SEM, FTIR, XRD, and release behavior of the scaffold has been performed to evaluate the features of the scaffolds. In fact, as-prepared Gel-HNT/ZA release 49% ZA in Phosphate Buffered Saline (PBS) within 21 days. The mechanical properties have been increased after adding HNTs and ZA from 10.27 to 26.18 MPa. Also, the water absorption has been increased after adding HNTs and ZA from 1.67 to 5.02 (g/g). Seeded human Adipose stem cells (hASCs) on the prepared scaffolds showed that the ZA effectively elevated the proliferation of the hASCs and also the MTT results proved the non-toxicity of all prepared scaffolds by high cell viability (˃80%). The osteogenic differentiation has been accelerated as displayed by ALP and Ca assay. The results propose that the HNTs-loaded Gelatin scaffold could control the releasing of ZA and its localized delivery at the defect site, simultaneously promoting the mechanical and osteogenesis ability of gelatin-based scaffolds.